Location of unaccessible implant surface areas during debridement in simulated peri-implantitis therapy - Valerie Steiger-Ronay; Andrea Merlini; Daniel B. Wiedemeier; Patrick R. Schmidlin; Thomas Attin; Philipp Sahrmann (BMC, 2017)
Abstract Background An in vitro model for peri-implantitis treatment was used to identify areas that are clinically difficult to clean by analyzing the pattern of residual stain after debridement with commonly employed instruments. Methods Original data from two previous publications, which simulated surgical (SA) and non-surgical (NSA) implant debridement on two different implant systems respectively, were reanalyzed regarding the localization pattern of residual stains after instrumentation. Two blinded examiners evaluated standardized photographs of 360 initially ink-stained dental implants, which were cleaned at variable defect angulations (30, 60, or 90°), using different instrument types (Gracey curette, ultrasonic scaler or air powder abrasive device) and treatment approaches (SA or NSA). Predefined implant surface areas were graded for residual stain using scores ranging from one (stain-covered) to six (clean). Score differences between respective implant areas were tested for significance by pairwise comparisons using Wilcoxon-rank-sum-tests with a significance level α = 5%. Results Best scores were found at the machined surface areas (SA: 5.58 ± 0.43, NSA: 4.76 ± 1.09), followed by the tips of the threads (SA: 4.29 ± 0.44, NSA: 4.43 ± 0.61), and areas between threads (SA: 3.79 ± 0.89, NSA: 2.42 ± 1.11). Apically facing threads were most difficult to clean (SA: 1.70 ± 0.92, NSA: 2.42 ± 1.11). Here, air powder abrasives provided the best results. Conclusion Machined surfaces at the implant shoulder were well accessible and showed least amounts of residual stain. Apically facing thread surfaces constituted the area with most residual stain regardless of treatment approach.